Melanocytes in the testes of Eupemphix nattereri (Anura, Leiuperidae): Histological, stereological, and ultrastructural aspects - Zieri, Rodrigo; Taboga, Sebastiao Roberto; De Oliveira, Classius (Wiley-Blackwell, 2007)
Ectothermic vertebrates have a well-developed system of melanin-containing cells, which localize in several organs and tissues and compose an extracutaneous pigmentary system. This research aimed at characterizing histological and ultrastructural patterns of pigmented cells in the testes of the anura Eupemphix nattereri (Steindachner, 1963), including the stereological and quantitative evaluation of this cell type in the gonads. Ten adult males were collected in Nova Itapirema, São Paulo, Brazil, and submitted to morphological studies with light and transmission electron microscopy. The testis presents a great number of large cells with many brown granules and long cytoplasmic processes. The pigmented cells found in the testis are structurally similar to melanocytes, characterized by large amounts of melanosomes. The cells may be in intimate contact with the same cell type, with myoid cells surrounded by a large amount of collagen fibers, Leydig cells, and next to fibroblasts. The distribution and amount of extracutaneous melanocytes is variable when other organs and membranes are analyzed, allowing the establishment of species-specific patterns for the extracutaneous pigmentary system.
Keywords: melanocyte; melanosomes; extracutancous pigmentary system; testes; Anura